1965
DOI: 10.1111/j.1469-8986.1965.tb02630.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Skin Potential and Skin Resistance Responses as Measures of Emotional Responsivity

Abstract: The purpose of this study was to compare gradients of skin resistance (SR) and skin potential (SP) responses generated by differing degrees of psychologically disturbing stimuli, and to determine the significance of the different wave forms of skin potential. SR and SP were simultaneously recorded during a word‐association test that included three levels of psychologically disturbing verbal stimuli. In addition to the a and b waves of the SP response, a second negative wave form, a2, was recorded. SR and all S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Burstein et al (1965) reported a high correspondence between the occurrence of SRRs and SPRs in reaction to emotionally significant stimuli with 20 participants (Sect. 2.5.1.3).…”
Section: Endosomatic Vs Exosomatic Recordingmentioning
confidence: 91%
See 1 more Smart Citation
“…Burstein et al (1965) reported a high correspondence between the occurrence of SRRs and SPRs in reaction to emotionally significant stimuli with 20 participants (Sect. 2.5.1.3).…”
Section: Endosomatic Vs Exosomatic Recordingmentioning
confidence: 91%
“…Burstein, Fenz, Bergeron, and Epstein (1965), who investigated SR and SP concurrently during a word association test, found that the correlations between the amplitude of the SP c-wave ( Fig. 2.14, Sect.…”
Section: Relationships Between Endosomatic and Exosomatic Measuresmentioning
confidence: 95%
“…a- and b-wave in Fig. 3A) both increase monotonically with emotion (Burstein et al, 1965), there is a lack of consensus about which SPR metric best characterizes the intensity of subject's emotion (Boucsein, 2012), suggesting that both waves carry some meaningful information. In an effort to select a single measure that is most representative of the whole response, we developed a new metric, SPR Magnitude , which is the average of the rectified SPR signal within a 4 s window from the onset of the a-wave (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies appear to have focused on SSR rather than SRR, but in the following discussion we assume that what is true for SSR is also valid for SRR, since the two are closely related. 24 Some authors reported that either the amplitude or the latency varies greatly on consecutive stimulation, 25'26 while Hoeldtke et al 27 observed no effect of habituation on latency in normal subjects. Danilov et a/.…”
Section: Discussionmentioning
confidence: 98%